Factors Associated with Adolescents' Readiness in Facing Puberty - Qonita Nabila Hidayati (Indonesian Journal of Administration and Health Research (IJAHR), 2025)
Adolescence is a transitional period from childhood to adulthood, marked by rapid growth and the development of reproductive abilities. This study aims to identify factors associated with adolescents' readiness for puberty at SMP Muhammadiyah 1 Pontianak. The research used a cross-sectional design with 81 seventh-grade students selected through systematic random sampling. Data were collected using a puberty readiness questionnaire and analyzed with the chi-square test (α = 0.05). The results showed that knowledge (p = 0.000, PR = 5.571), sources of information (p = 0.000, PR = 16.818), permissive parental communication (p = 0.003, PR = 2.144), and peer support (p = 0.000, PR = 2.828) were significantly related to puberty readiness. Democratic communication patterns and authoritarian communication patterns were not significantly related. Based on these findings, it is recommended that puberty and reproductive health education be provided early through various accessible sources of information for adolescents, and that open communication between parents and children, especially through permissive communication, be strengthened. Additionally, fostering positive peer support is essential in helping adolescents prepare for puberty.Masa remaja adalah periode transisi dari kanak-kanak menuju dewasa, ditandai dengan pertumbuhan pesat dan perkembangan kemampuan reproduksi. Penelitian ini bertujuan untuk mengetahui faktor yang berhubungan dengan kesiapan remaja menghadapi pubertas di SMP Muhammadiyah 1 Pontianak. Penelitian menggunakan desain cross sectional dengan 81 sampel siswa kelas VII yang dipilih secara systematic random sampling. Data dikumpulkan melalui kuesioner kesiapan pubertas dan dianalisis dengan uji chi-square (α = 0,05). Hasil penelitian menunjukkan bahwa pengetahuan (p = 0,000, PR = 5,571), sumber informasi (p = 0,000, PR = 16,818), komunikasi orang tua dengan pola permisif (p = 0,003, PR = 2,144), dan dukungan teman sebaya (p = 0,000, PR = 2,828) berhubungan signifikan dengan kesiapan pubertas. Pola komunikasi demokratis, pola komunikasi otoriter tidak berhubungan signifikan. Berdasarkan temuan ini, disarankan agar pendidikan pubertas dan reproduksi diberikan sejak dini melalui berbagai sumber informasi yang dapat diakses remaja, serta memperkuat komunikasi terbuka antara orang tua dan anak, terutama dengan pola komunikasi permisif. Selain itu, penting juga untuk mendorong dukungan teman sebaya yang positif dalam membantu remaja mempersiapkan diri menghadapi pubertas.